Low-Frequency Noise Assessment of the Oxide Trap Density in Thick-Oxide Input-Output Transistors for DRAM Applications. (31st March 2016) - Simoen, E.; Ritzenthaler, R.; Cho, M.-J.; Schram, T.; Horiguchi, N.; Aoulaiche, M.; Spessot, A.; Fazan, P.; Claeys, C.
Abstract : The impact of the implementation of a high-κ/metal-gate (HKMG) stack on the oxide integrity of input-output (I/O) pMOSFETs for DRAM periphery applications is investigated by means of low-frequency (LF) noise spectroscopy. It is shown that the predominant 1/f noise is governed by number fluctuations, irrespective of the details of the gate stack. However, the trap density in the 5 nm SiO2 gate oxide, derived from the noise power spectral density is significantly increased by the application of the HKMG and/or Al2 O3 cap and the subsequent diffusion anneal at 900°C.